Disaster Communication and Civic Voluntarism during COVID-19 Pandemic: The Case of Bandung - Ismail, Oki Achmad; Wijaksono, Dimas Satrio (Program Studi Ilmu Komunikasi, 2024)
This research examined communication strategies in increasing volunteer participation and communication methods in improving disaster communication skills. This research also identified challenges and obstacles in implementing civic voluntarism in the city of Bandung. This research used a qualitative method with a case study approach at the Bandung City Fire and Disaster Management Service. Data was collected through interviews, documents, observations and literature studies. The research results show that the people of Bandung City have a movement based on civic voluntarism in dealing with Covid 19. Technical guidance is used to encourage civic voluntarism. Technical guidance is used to train skilled volunteers in carrying out disaster communications. By having knowledge, reliability and communication skills, volunteers become one of the strengths of disaster communication in the city of Bandung. There are three main obstacles in its implementation, namely differences in education level, motivation and time availability among volunteers.